2010
DOI: 10.1002/humu.21282
|View full text |Cite
|
Sign up to set email alerts
|

LPIN1 gene mutations: a major cause of severe rhabdomyolysis in early childhood

Abstract: Autosomal recessive LPIN1 mutations have been recently described as a novel cause of rhabdomyolysis in a few families. The purpose of the study was to evaluate the prevalence of LPIN1 mutations in patients exhibiting severe episodes of rhabdomyolysis in infancy. After exclusion of primary fatty acid oxidation disorders, LPIN1 coding sequence was determined in genomic DNA and cDNA. Among the 29 patients studied, 17 (59%) carried recessive nonsense or frameshift mutations, or a large scale intragenic deletion. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 30 publications
3
149
1
4
Order By: Relevance
“…the presence of myoglobin in urine, which is usually linked to destruction of skeletal muscle fibers, the latter also known as rhabdomyolysis) or statin-induced myopathy (38). An additional study reported severe early childhood myoglobinuria due to an in-frame intragenic Lpin1 deletion, removing a large part of the Lipin 1 CLIP domain (exons 18 and 19) but preserving its transcriptional LXXIL motif (39). Unfortunately, the PNS status of these patients was not evaluated and these patients may be too young to clearly detect a potentially mild WAT-related phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…the presence of myoglobin in urine, which is usually linked to destruction of skeletal muscle fibers, the latter also known as rhabdomyolysis) or statin-induced myopathy (38). An additional study reported severe early childhood myoglobinuria due to an in-frame intragenic Lpin1 deletion, removing a large part of the Lipin 1 CLIP domain (exons 18 and 19) but preserving its transcriptional LXXIL motif (39). Unfortunately, the PNS status of these patients was not evaluated and these patients may be too young to clearly detect a potentially mild WAT-related phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the gene encoding lipin 1 (LPIN1) have been identified as a cause of recurrent, early-onset, pediatric rhabdomyolysis and myoglobinuria (OMIM#268200) (Zeharia et al 2008;Michot et al 2010Michot et al , 2012. Rhabdomyolysis is an acute syndrome due to extensive injury of skeletal muscle resulting in the release of intracellular metabolites and proteins, including creatine kinase and myoglobin, into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Classes of inherited metabolic disorders associated with recurrent rhabdomyolysis include glycogen storage diseases, fatty acid oxidation defects, and mitochondrial disorders (Tonin et al 1990;Kelly and Strauss 1994;Bennett 2010;Zutt et al 2014). Recently, homozygous mutations in LPIN1 were identified as a common cause of recurrent rhabdomyolysis in pediatric patients, and more than 50% of infants and children with unexplained severe rhabdomyolysis in a European population may have pathologic mutations in LPIN1 (Zeharia et al 2008;Michot et al 2010Michot et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Метаболические нарушения [6][7][8][9][10][11]: -дефицит окисления жирных кислот [7,10,11]; -дефицит липина-1 [12][13][14]; -нарушение метаболизма гликогена и гликолиза [7,8];…”
Section: термолабильность рассматривается как один из факторов провоunclassified